First records of some coral reef-associated brachyuran crabs from the Nicobar archipelago, India - Padate, Vinay P.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zootaxa, 2024)
The coral reefs off the Andaman and Nicobar archipelagos harbour some of the world’s diverse reef-associated crustacean fauna, which have not been adequately surveyed. A recent faunal survey in the Andaman Sea on-board the Fishery Oceanographic Research Vessel Sagar Sampada (cruise number 388) revealed a rich diversity of coral reef-associated brachyuran crabs. The article reports four genera, Singhaplax Serène & Soh, 1976, Cavoportunus Nguyen & Ng, 2010, Cyrtocarcinus Ng & Chia, 1994 and Visayax Mendoza & Ng, 2008 occurring in Indian waters for the first time. Seven species namely Singhaplax ockelmanni (Serène, 1971), Urnalana angulata (Rathbun, 1911), Pseudolambrus confragosus (Calman, 1900), Cavoportunus dubius (Laurie, 1906), Cyrtocarcinus truncatus (Rathbun, 1906), Visayax osteodictyon Mendoza & Ng, 2008, and Xanthias joanneae Mendoza, 2013, are likewise reported for the first time from Indian waters.